2020
DOI: 10.1108/rege-03-2019-0041
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity, governance and dividend policy in Brazil

Abstract: PurposeConsidering that the heterogeneity in the composition of deliberation and management bodies can promote a differentiated impact on earnings distribution policies of companies, the purpose of this paper is to examine the marginal influence of female participation on the board of directors and executive board regarding decisions associated with dividend policy in companies operating in Brazil.Design/methodology/approachThe sample is composed of non-financial companies listed on the B3 Stock Exchange betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
3
8
0
1
Order By: Relevance
“…Consequently, women directors are more inclined to set higher dividend payout ratios. Our finding is consistent with Ye et al (2019), Sanan (2019) and Almeida et al (2020) whose studies indicated that the presence of women on the board improves corporate governance practices and contributes to higher dividend payout.…”
Section: Board Gender Diversitysupporting
confidence: 92%
See 3 more Smart Citations
“…Consequently, women directors are more inclined to set higher dividend payout ratios. Our finding is consistent with Ye et al (2019), Sanan (2019) and Almeida et al (2020) whose studies indicated that the presence of women on the board improves corporate governance practices and contributes to higher dividend payout.…”
Section: Board Gender Diversitysupporting
confidence: 92%
“…Therefore, firms with more female directors on the boards appear to face lower litigation risk, which, perhaps, in part explains higher payouts. By improving corporate governance and the protection of shareholder interests, board gender diversity can encourage the payment of corporate dividends (Benjamin and Biswas, 2019;Almeida et al, 2020). The results are also consistent with the predictions of resource dependence theory according to which female directors bring their better experiences, skills and abilities to the board, which increases board efficiency (Hillman and Dalziel, 2003).…”
Section: Board Gender Diversitysupporting
confidence: 76%
See 2 more Smart Citations
“…Komposisi direksi wanita pada perusahaan Indonesia cenderung rendah, sehingga menyebabkan pengaruh direksi wanita menjadi insignifikan. Kondisi demikian juga dihasilkan pada penelitian (Almeida et al, 2020). Namun hasil pada model kedua menunjukkan bahwa direksi wanita memberikan pengaruh signifikan negatif terhadap DP2.…”
Section: Pembahasanunclassified